Pectinase production by aspergillus niger and its applications in fruit juice clarification - Wagh, Vrushali; Patel, Hirvitaben; Patel, Nafisa; Vamkudoth, Koteswara Rao; Ajmera, Shanthipriya (Journal of Pure and Applied Microbiology, 2022)
Pectinases (EC 3.2.1.15) are a class of enzymes that catalyze the depolymerization or de-esterification reactions that degrade pectic substances. In the present study, we have isolated the Aspergillus niger strain from soil samples, in India and evaluated pectinase production. The highest pectinase producing A. niger strain was further evaluated and optimized with various agricultural wastes. Plackett-Burman design (PBD) and Central composite design ‘(CCD)’ were used to determine the best parameters for maximum pectinase production. Pectinase activity was increased to 99.21 U/ml after optimizing the production medium using PBD and CCD statistical analysis. A positive correlation of pectinase activity between predicted (112.65 U/ml) and experimental (99.21 U/ml with SD=0.005) optimum was observed. Maximum pectinase was produced by A. niger under submerged fermentation, utilizing orange peel, which is a cost-effective, adaptable, and environmentally friendly approach. The partially purified pectinase showed significant application for apple juice clarification and showed the ability to degrade pectin and therefore the colour change was observed in apple juice within 120 min. Maximum pectinase was produced by A. niger using agricultural waste orange peel under submerged fermentation which is an economical, versatile and eco-friendly process and pectinase showed a significant application for apple juice clarification.